Efficacy of new generation herbicides for weed management in dry direct seeded system of rice - Arya, S.R.; Ameena, M. (Annals of Agricultural Research, 2017)
The present study was conducted during kharif season of May to September 2014 to evaluate the weed control efficiency of low dose new generation herbicides in semi dry system of ricecultivation. Results of the study revealed substantial reduction in weed population and biomass in all the herbicide treated plots compared to weedy check. Pre-emergent herbicide application followed by either hand weeding at 40 DAS or application of post emergent herbicides recorded higher weed control efficiency in comparison with hand weeding twice (20 and 40 DAS). Bensulfuron methyl + pretilachlor @ 60 + 600 g ha–1 and pyrazosulfuron ethyl @ 25 g ha–1 were found promising broad spectrum herbicides for early season weed control in semi dry system of rice cultivation. Hand weeding at 20 and 40 DAS (T10) recorded lowest weed density, weed dry weight and highest weed control efficiency. Hence pre-emergence application of either bensulfuron methyl + pretilachlor @ 60 + 600 g ha–1 or pyrazosulfuron ethyl @ 25 g ha–1 on the next day of sowing followed by post emergence application of azimsulfuron @ 30 g ha–1 at 25 DAS could be recommended as the most effective weed management practice for dry direct seeded system of rice.